LANGUAGE-IMAGE INTEGRATIVE PROCESSING IN INSTRUCTIONAL CONTEXTS: A COGNITIVIST PERSPECTIVE - Perales López, José César; Romero Barriga, Juan Francisco (Anales de Psicología / Annals of Psychology, 2005)
Didactical images are powerful tools to complement written and oral language comprehension in instructional situations. The present work summarizes the most relevant studies on conjoint processing of language and visual displays, focusing on those situations in which the image complements a narration (multimedia presentations, oral communications…) or a text (textbooks, online training materials…). On the base of the well-established ground of human perception, attention and memory research, a cognitive model of text-image integrative processing is proposed –also applicable, taking into account certain considerations, to narration-image integrated presentations-. The model overcomes some of the limitations of previous approaches, and stresses the importance of executive processing in language and image interpretation, and in establishing referential links between their correspondent mental codes. The model specifies the executive functions involved in the elaboration of unitary-distributed representations that include visuospatial and propositional information (stabilization), and in sequencing the series of actions that the learner carries out in a real-time fashion during integration tasks (sequencing).